Effect of Infant Massage by Mothers on Maternal Attachment Behavior in Infants Hospitalized in Neonatal Care Units - Soroor Sohrabi; Zahra Ahmadi; Ziba Mosayebi; Hamid Haghani (Tehran University of Medical Sciences, 2014)
Background & Aim: Several studies have indicated that hospitalizing infants causes disruption on mother-infant attachment. The aim of this study was to assess the effect of infant massage by mothers on maternal attachment behavior in infants hospitalized in the neonatal care units .   Methods & Materials: In this clinical trial, 42 mothers and their neonates were recruited and randomly allocated to the intervention and control groups. Mothers in the intervention group received training by means of educational movies about practical exercises on how to massage the infants. The trained mothers used massage techniques on their infants for five days. The process lasted 15 minutes. The attachment of the mothers on their infants was assessed before and on the day 5 after the massage. Data were collected using the scale of mother-to-infant attachment. Data were analyzed using the Chi-squared test, Fisher's exact test and the t-test in the SPSS-19 .    Results: There were no differences between the two groups in terms of demographic variables and the mean of maternal attachment at baseline (P>0.05). Five days after the massage, there were statistically significant differences between the two groups in the mean maternal attachment (P<0.001) .   Conclusion: According to the role of massage in attachment behavior, this traditional care is recommended to be used in neonatal units .